Air Purifier Property, Assessment and Applications - Xu, Zhonglin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses the development, types and application principles of portable air purifiers in China. It analyzes the theoretical characteristics of air purifiers under various operational conditions, and points out that the term "Clean Air Delivery Rate" cannot be used to precisely reflect the problems that occur under various operational conditions. By comparing theoretical and measured data, it highlights the main features of air purifiers and key points in the design process for different applications. Calculation methods for the indoor particle concentration and the self-purification time are also provided. The book describes the conditions for window opening in smog and for selecting air purifiers, and proposes a new method for improving their measurement. In closing, it includes a new assessment index. .
Introduction -- High-voltage Electrostatic Absorption -- UV Irradiation -- Fibrous Layer Filter -- Operational Property of Air Purifier -- Application Property of Air Purifier -- Calculation of Pollutant Load to Air Purifier -- Calculation on Cleaning Capability of Air Purifier -- Test and Assessment of Air Purifier.
Keywords: Buildings -- Environmental engineering; Pollution; Machinery; Building Physics, HVAC; Pollution; Machinery and Machine Elements